SCOPE: Examining Technology-Enhanced Collaborative Care Management of Depression in the Cancer Setting - Mittal, Anant; Karkar, Ravi; Suh, Jina; Williams, Spencer; Andris, Lydia M.; Bates, Nicole; Bauer, Amy M.; Lostutter, Ty W.; Fann, Jesse R.; Fogarty, James; Hsieh, Gary; Jones, Tae; et al. (Proceedings of the ACM on Human-Computer Interaction, 2025)
Collaborative care management is an evidence-based approach to integrated psychosocial care for patients with comorbid cancer and depression. Prior work highlights challenges in patient-provider collaboration in navigating parallel cancer care and psychosocial care journeys of these patients. We design and deploy SCOPE, a platform for technology-enhanced collaborative care combining a patient-facing mobile app with a provider-facing registry. We examine SCOPE through a total of 45 interviews with patients and providers conducted in SCOPE's 15 months of design and development and 24 Months of SCOPE's deployment for actual care in 6 cancer clinics. We find that: (1) SCOPE supported patient engagement in its underlying collaborative care and behavioral activation interventions, (2) patient-generated data in SCOPE improved patient-provider collaboration between and within in-person sessions, (3) SCOPE supported providers in delivering care and improved care team collaboration, (4) experience with SCOPE created evolving expectations for collaboration around data, and (5) SCOPE's deployment in actual care surfaced important implementation barriers. We discuss the implications of our findings in terms of designing for engagement with behavioral health interventions, negotiating patient data sharing and provider responsiveness, supporting personalized self-tracking goals in evidence-based interventions, exploring the role of digital health navigators in technology-enhanced care, and the need for flexibility in aligning technology-supported interventions to patient needs.